Electromagnetic bone segment tracking to control femoral derotation osteotomy—A saw bone study - Geisbüsch, Andreas; Auer, Christoph; Dickhaus, Hartmut; Niklasch, Mirjam; Dreher, Thomas (Journal of orthopaedic research, 2017)
ABSTRACT Correction of rotational gait abnormalities is common practice in pediatric orthopaedics such as in children with cerebral palsy. Femoral derotation osteotomy is established as a standard treatment, however, different authors reported substantial variability in outcomes following surgery with patients showing over‐ or under‐correction. Only 60% of the applied correction is observed postoperatively, which strongly suggests intraoperative measurement error or loss of correction during surgery. This study was conducted to verify the impact of error sources in the derotation procedure and assess the utility of a newly developed, instrumented measurement system based on electromagnetic tracking aiming to improve the accuracy of rotational correction. A supracondylar derotation osteotomy was performed in 21 artificial femur sawbones and the amount of derotation was quantified during the procedure by the tracking system and by nine raters using a conventional goniometer. Accuracy of both measurement devices was determined by repeated computer tomography scans. Average derotation measured by the tracking system differed by 0.1° ± 1.6° from the defined reference measurement . In contrast, a high inter‐rater variability was found in goniometric measurements (range: 10.8° ± 6.9°, mean interquartile distance: 6.6°). During fixation of the osteosynthesis, the tracking system reliably detected unintentional manipulation of the correction angle with a mean absolute change of 4.0° ± 3.2°. Our findings show that conventional control of femoral derotation is subject to relevant observer bias whereas instrumental tracking yields accuracy better than ±2°. The tracking system is a step towards more reliable and safe implementation of femoral correction, promising substantial improvements of patient safety in the future. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:1106–1112, 2017. Correction of rotational gait abnormalities is common practice in pediatric orthopaedics, but substantial variability in outcomes have been reported. This study was conducted to assess the utility of an instrumented measurement system for intraoperative derotation control based on electromagnetic tracking. Average derotation measured by the tracking system differed 0.1° ± 1.6° from the defined CT reference measurement. Our findings show that conventional control of femoral derotation is subject to relevant observer bias whereas instrumental tracking yields accuracy better than ±2°.